LEISURE NOSTALGIA SCALE: THE VALIDITY AND RELIABILITY STUDY - Balcı, Velittin; Tez, Özge Yavaş (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2019)
The aim of this study was to adapt the “Leisure Nostalgia Scale” (LNS) which was developed by Cho, Pyun ve Wang (2019) to measure for the determination of feelings of nostalgia of leisure participants. The study sample consisted of 214 (female 100 Mage = 32.99; Sd= 13.61 years; male 114 Mage = 31.44; Sd= 12.37 years) participants with different leisure experiences. The original version of the scale consists of 5 sub-dimensions and 33 items. Descriptive statistics, item analysis, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), Split-Half Analysis, and Cronbach’s Alpha analysis were performed to analyze data. EFA and CFA factor analyses showed, the Turkish version of the leisure nostalgia scale was consisted of 3 sub-dimensions with 15 items. The factor loadings of the scale were ranged between 0.51-0.94. Reliability coefficients for the sub-dimensions ranged from 0.93 (social memories), 0.89 (group rituals) and 0.81 (spatial memories). Split-Half correlation coefficients of the scale were found (0.81-0.78). Results finally indicated that LNS was a valid and reliable measurement tool to be used for measuring nostalgic emotional of Turkish leisure participants.